Is Perioperative Dexmedetomidine Associated With a Reduced Risk of Perioperative Neurocognitive Disorders Following Cardiac Surgery? A Systematic Review and Meta-Analysis With Trial Sequential Analysis of Randomized Controlled Trials - Xiong, Xinglong; Chen, Dongxu; Shi, Jing (Frontiers in Medicine, 2021)
Background: To assess the effect of dexmedetomidine on the reducing risk of perioperative neurocognitive disorders (PND) following cardiac surgery. Methods: A systematic review and meta-analysis with trial sequential analysis of randomized controlled trials was performed. PubMed, Embase, Cochrane Library and CNKI databases (to August 16, 2020) were searched for relevant articles to analyze the incidence of PND for intraoperative or postoperative dexmedetomidine administration after cardiac surgery. PND included postoperative cognitive dysfunction (POCD) and postoperative delirium (POD). Results: 24 studies with 3610 patients were included. Compared with the control group, the incidence of POD in the dexmedetomidine group was significantly lower (OR 0.59, 95% CI 0.43 to 0.82, P = 0.001), with ﬁrm evidence from trial sequential analysis. Subgroup analyses conﬁrmed that dexmedetomidine reduced the incidence of POD with ﬁrm evidence following CABG surgery (OR 0.45, 95% CI 0.26 to 0.79, P = 0.005), and intervention during the postoperative period (OR 0.48, 95% CI 0.34 to 0.67, P < 0.001). Additionally, the incidence of POD in the dexmedetomidine group was also decreased in mixed cardiac surgery (OR 0.68, 95% CI 0.47 to 0.98, P = 0.039). Irrespective of whether ‘CAM/CAM-ICU’ or ‘other tools’ were used as diagnostic tools, the results showed a decreased risk of POD in the dexmedetomidine group. There was no significant difference in the incidence of POCD (OR 0.47, 95% CI 0.22 to 1.03, P = 0.060) between the two groups, but this result lacked ﬁrm evidence from trial sequential analysis. Conclusion: The administration of dexmedetomidine during the perioperative period reduced the incidence of POD in patients after cardiac surgery, but there was no significant benefit in the incidence of POCD. The eﬀect of dexmedetomidine on the incidence of POD or POCD following different types of surgery, and the optimal dose and timing of dexmedetomidine warrant further investigation.